DESAIN FURNITUR KABINET MULTIFUNGSI PADA INTERIOR YAYASAN RUMAH PAGI BAHAGIA DI BINTARO - Ismanto, Adi (Jurnal Serina Abdimas, 2023)
The interior design of Rumah Pagi Bahagia Foundation has been created since the end of 2021 as part of PKM activities that aim to meet the needs of activities and facilities in accordance with the vision of mis and informal learning activity programs. The ongoing pandemic condition is a bit of an obstacle for the Foundation in carrying out activities with room conditions that are still in the process of carrying out construction. Currently, the room divider still uses a simple gypsum partition to separate several rooms. Based on the design concept that has been approved with the theme concept "In The Library Exhibition" the Rumah Pagi Foundation plans to make multifunctional cabinet furniture that will be the main supporting furniture in the room to facilitate non-formal learning activities which is one of the main programs of the Rumah Pagi Bahagia Foundation. The method used is an observation method of collecting data and references related to user ergonomics which is continued by the method of exploring ideas or ideas to produce a schematic design that is functionally and aesthetically appropriate. The results of the multifunctional cabinet furniture design of the Rumah Pagi Bahagia Foundation are one part of the overall interior design process of the shophouse building. Through the design development process, the design of multifunctional cabinet furniture has been completed and successfully met the needs according to the design theme concept by producing more detailed material specifications, module dimensions that match ergonomics and visual imagery in accordance with the character of the vision, mission, managers, users and the activity program of the Rumah Pagi Bahagia Bintaro Foundation. This design will be continued with the construction process and periodic supervision so that it can produce products that are in accordance with the expected quality. Desain interior Yayasan Rumah Pagi Bahagia telah dibuat semenjak tahun 2021 akhir sebagai bagian dari kegiatan PKM yang bertujuan untuk memenuhi kebutuhan aktivitas dan fasilitas sesuai dengan visi mis serta program kegiatan pembelajaran informal. Kondisi pandemi yang masih berlanjut sedikit menjadi kendala untuk Yayasan dalam melakukan kegiatan dengan kondisi ruangan yang masih dalam proses pelaksanaan konstruksi. saat ini pembatas ruangan masih mengunakan partisi gypsum sederhana untuk memisahkan beberapa ruangan. Berdasarkan konsep desain yang telah disetujui dengan konsep tema “In The Library Exhibition” Yayasan Rumah Pagi berencana akan membuat furnitur kabinet multifungsi yang akan menjadi furnitur penunjang utama pada ruangan untuk memperlancar kegiatan pembelajaran non formal yang menjadi salah satu program utama dari Yayasan Rumah Pagi Bahagia. Metode yang digunakan adalah metode observasi pengumpulan data dan referensi terkait ergonomic pengguna yang dilanjutkan dengan metode eksplorasi ide atau gagasan untuk menghasilkan skematik desain yanhg tepat secara fungsi dan estetika. Hasil perancangan furnitur kabinet multifungsi Yayasan Rumah Pagi Bahagia merupakan salah satu bagian dari keseluruhan proses perancangan interior bangunan ruko. Melalui proses pengembangan desain, perancangan furnitur kabinet multifungsi telah selesai dan berhasil memenuhi kebutuhan sesuai konsep tema desain dengan menghasilkan spesifikasi material yang lebih detail, dimensi modul yang sesuai ergonomi serta visual citra yang sesuai dengan karakter visi, misi, pengelola, pengguna serta program kegiatan Yayasan Rumah Pagi Bahagia Bintaro. Perancangan ini akan dilanjutkan dengan proses konstruksi dan pengawasan berkala sehingga dapat meghasilkan produk yang sesuai dengan kualitas yang diharapkan.